Martensitic transformation strain and stability of Ni50-x-Ti50-Cox (x=3,4) strips obtained by twin-roll casting and standard processing techniques - Isola, Lucio Manuel (2016)
The martensitic transformation properties (maximum strain, residual strain and transformation stability) of Ni50-x-Ti50-Cox strips produced by twin-roll casting (TRC) and standard casting (SC) were compared. A complete microstructural characterization was carried out on both samples using optical microscopy, transmission electron microscopy (TEM), electron backscattering diffraction (EBSD-SEM), energy dispersive X-ray spectroscopy (EDS-SEM), X-Ray diffraction and differential scanning calorimetry (DSC). According to the results obtained by DSC and load-biased thermal-cycling measurements, the TRC strip is more stable and has lower residual strain than the SC strip for loads below 90 MPa. Using the austenitic texture of each strip, the recoverable strain upper bounds of the martensitic transformation (Sachs' bound) were calculated. A comparison between the measured maximum recoverable strain and the Sachs' bound, allows us to discuss how the particular microstructures produced by the two production techniques affect the strip's shape memory properties.